The Application of Routing of OSPF and EIGRP using the Method Redistribute to Improve the Efficiency of The Network - Ari Ramadhan Wibowo; Anton Anton; Puji Astuti (Kresnamedia Publisher, 2020)
Cyber ​​Art Group Indonesia is the Head Office in the Ciputat area, South Tangerang which is engaged in wedding planning and has one branch in Depok, West Java. Currently, between branches and head offices, data retrieval, and data transmission is done via email. And in branches there is no local network available, the local network is only at the head office. If you want to pick up or send, the marketing at the branch contacts the head office to send files, this creates obstacles for employees both at the branch and head office. Because all data is stored on the central server, if there is a need, it can be retrieved at any time. So for that researchers here create a local network between the branch office and the head office. By using the Redistribution Router method, data retrieval and sending to the server can be seen whether the time is faster by using the Throughput, Delay, and Packet loss measurement parameters. Connecting multiple routers as gateways and implementing OSPF and EIGRP routing makes data transfer easier and more efficient on multiple routers. After installing the local network between the branch and the head office, it is tested with a package size of 32 bytes, namely 100%. For the Packet loss value with a packet size of 32 bytes in the first and second experiments, it produces a value of 0%, where no packet is lost.